Optimasi Parameter Proses Sealing Pada Kemasan Fleksibel Laminasi PET/ALU/PE/LLDPE Menggunakan Metode Design Of Experiments (DOE) - Rahmadi, Septian; Fattahillah, Rangga Wahyu; Suhaeri, Suhaeri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
High seal integrity is critical for multilayer flexible packaging (PET/ALU/PE/LLDPE) to ensure product quality and safety. This study aims to optimize heat-sealing parameters—temperature, pressure, and time—using Design of Experiments (DOE) within a response surface approach. A full-factorial design (3×3×3) was applied, involving three levels for each factor (temperature: 120–140 °C; pressure: 2–4 bar; time: 0.5–1.5 s), resulting in 27 experimental runs. Seal strength was measured in g/15 mm according to ASTM F88/F88M, and analyzed using ANOVA and quadratic regression modeling. Results indicate that all main effects and interactions are statistically significant (p < 0.05), with temperature and time as dominant factors, and a substantial temperature×pressure interaction. The model demonstrated excellent fit (Adjusted R² ≈ 97%). Optimization using Response Optimizer identified the best conditions at 134.7 °C, 4.0 bar, and 1.18 s, predicting seal strength of approximately 5,812 g/15 mm with desirability ≈ 0.95. These findings provide actionable guidance for improving seal quality, reducing defects, and enhancing process efficiency in flexible packaging manufacturing.